Sewage wastewater: A potential energy source for boosting power generation in the Khartoum state of Sudan. (December 2022) - Farouk, Hazir; Lang, Andrew; Tahir, Furqan; Al-Ghamdi, Sami G.
Abstract: In this time of increasing consciousness of global warming and the likelihood that fossil fuels – particularly crude oil and natural gas – will become less available and more costly, all countries are looking at their options for maintaining energy supply over the coming decades. The formation and adoption of cutting-edge, cost-effective, and efficient biomass-to-energy technologies will meet a sizeable portion of Sudan's energy needs and have a positive cascading effect on other economic sectors as part of the overall effort to better utilize all forms of biomass for the efficient provision of energy in Sudan. This study looks at the major opportunity to produce energy from sewage wastewater in Khartoum State in Sudan. The sewage wastewater and the associated biomass are estimated and analyzed for heat and electricity production. It was found that the biogas generated from treatment plants in Khartoum State could produce about 94 MW and 188 MW of electricity and heat, respectively. In addition, the social and environmental aspects are also discussed.